2019
DOI: 10.1007/s10198-019-01069-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of European, Polish, Slovenian and British EQ-5D-3L value sets using a Hungarian sample of 18 chronic diseases

Abstract: Background In the Central and Eastern European region, the British EQ-5D-3L value set is used commonly in quality of life (QoL) studies. Only Poland and Slovenia have country-specific weights. Our study aimed to investigate the impact of value set choice on the evaluation of 18 chronic conditions in Hungary. Methods Patients’ EQ-5D-3L index scores were calculated using the VAS-based Slovenian and European and the time-trade-off-based Polish and British value sets. We pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…The data on the preferences of adults towards health states were collected in the IMPACT HTA study, with a goal to explore whether values for health states for children (11)(12)(13)(14)(15)(16)(17) years of age) estimated by the general population (age 18+) differ from values obtained from adolescents themselves for the same health states. In this context, standard methods to elicit preferences, namely the DCE (discrete choice experiment) valuations for EQ-5D-Y-3L health states in combination with TTO (time trade-off ) were applied to collect the preferences from the respondents with the aim to develop EQ-5D-Y-3L value set.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data on the preferences of adults towards health states were collected in the IMPACT HTA study, with a goal to explore whether values for health states for children (11)(12)(13)(14)(15)(16)(17) years of age) estimated by the general population (age 18+) differ from values obtained from adolescents themselves for the same health states. In this context, standard methods to elicit preferences, namely the DCE (discrete choice experiment) valuations for EQ-5D-Y-3L health states in combination with TTO (time trade-off ) were applied to collect the preferences from the respondents with the aim to develop EQ-5D-Y-3L value set.…”
Section: Data Collectionmentioning
confidence: 99%
“…The application of an arbitrary dataset without adjustments might lead to biases, and finally, to poor health policy decisions. The scarcity of EQ-5D population norms in the Central and East European (CEE) region is a concern from both public health and HTA perspective [15].…”
Section: Introductionmentioning
confidence: 99%
“…The Slovenian TTO-based value set, being a choice-based method, is recommended for use in all studies, including economic analysis. Systematic pairwise comparison across all conditions and value sets in previous studies (32) revealed the greatest differences between the TTO and VAS-based value sets, as well as the varying sensitivity of the disease burden evaluations of chronic disease conditions to the choice of value sets. Therefore, using a VAS value set in the presence of newly developed TTO value set in Slovenia would unnecessarily produce incomparable results.…”
Section: Discussionmentioning
confidence: 99%
“…However, in order to allow for comparisons with previous studies where VAS values were used due to the absence of a TTO-based value set, it is suggested to present VAS-based results in parallel. Another option is also the presentation of the results in parallel with the UK TTO value set, given that it has been the most used value set in the region (33).…”
Section: Discussionmentioning
confidence: 99%
“…We also estimated the proportion of states with values less than zero. The statistical analysis was conducted using R (27), charting was done using the ggplot2 package (28) and basic data manipulation with the dplyr package (29).…”
Section: Slovenian Eq-5d-3l Value Setmentioning
confidence: 99%